UK healthcare support workers and the COVID-19 pandemic: an explorative analysis of lived experiences during the COVID-19 pandemic. Issue 1 (2nd January 2023) - Kasdovasilis, Pavlos; Cook, Neil; Montasem, Alexander
ABSTRACT: Support workers are an underrepresented profession that receives less attention with a high degree of responsibilities. The aim of this study was to explore the lived experiences of healthcare support workers within the care sector during the COVID-19 pandemic. This is a qualitative semi-structured interview study using an interpretative phenomenology (IP) framework. Fifteen (15) support workers were interviewed while all COVID-19 restrictions from the government were still in place. We identified five main themes: (1) challenging experiences; (2) coping mechanisms; (3) emotions and behaviors arising from the COVID-19 pandemic; (4) external interest on support worker's health; (5) take-home message from the COVID-19 pandemic. The organization selected for the research is a good representative of how care organizations operate within the UK both in terms of policies and staff selection.